Socio-Religious Values in The Manyanggar Banua Ceremony in The Barikin Sungai Tengah Hulu Selatan Community Kalimantan, Indonesia - Riduan, M.; Putro, Herry Porda Nugroho; Sriwati; Zakaria, Nurhijrah Binti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
The research aims to analyze the social and religious values of the Menyanggar Banua Ceremony in Barikin Community in Hulu Sungai Tengah, South Kalimantan, which is also knwn as Babungan Tahun and Annual Wayang. The Menyanggar Banua ritual aims to purify the village by removing all negative elements that disturb the welfare of the community. This research uses historical methods, which include heuristics, criticism, interpretation and historiography. The initial stage of this research includes heuristics, collecting historical sources, primary and secondary data. The next stages include External Criticism and Internal Criticism. The results of this research show that the Menyanggar Ceremony in the Barikin Community in Hulu Sungai Tengah Regency, South Kalimantan Province has religious meaning, especially in the beliefs and sacredness associated with the masks used in the ceremony, such as the Sangkala Mask or Batarakala which is believed by Zuriah Datu Taruna. The Manyanggar Banua ceremony in the village of Barikin Hulu Sungai Tengah contains important social values ​​such as Gaturahmi, Mutual Cooperation, Cooperation and Gotong Royong. These values ​​are essential for the proper conduct of ceremonies and provide valuable lessons for social life.